Penggunaan Media Sosial Tik Tok dan Dampaknya Terhadap Pendidikan Akhlak Remaja - Khoir, Arifatul; Ikhwan Aziz Q; Rina Mida Hayati (Sekolah Tinggi Ilmu Tarbiyah Bustanul `'Ulum Lampung Tengah, 2023)
Social media is a platform for public around the world to discuss their opinions and issues. Children are growing up surrounded by mobile devices and interactive social networking sites such as Tik Tok. This phenomenological study explored the impact of social media on the moral education of adolescences at Sputih Agung Lampung Tengah. Employing the qualitative research method with a case study approach, the research solicited 20 adolescences and their parents at Sputih Agung Lampung Tengah. The findings showed that social media has two sides for adolescences. Using of social media has a positive and negative impact for adolescences.This study concluded that parents dan teachers play a deeper role in shaping the character of the child through digital literacy. Therefore, this research recommends synergy between schools as formal education, parents as informal education, and the society as a laboratory for children's